The Mediating Effect of CEO Power on Creditor Rights and Capital Structure among Firms Listed in Nairobi Securities Exchange - Mutwol, Philemon K.; Cheboi, Josephat K.; Saina, Ernest (African Journal of Education,Science and Technology (AJEST), 2022)
Capital is an important component of all types of business activities, which are determined by the size and nature of the company. Various sources of capital can be used to raise funds. The company will earn high profits and be able to pay out more dividends to its shareholders if it maintains a sufficient and adequate level of capital. Firms confront difficulties in determining the appropriate combination of equity and debt that optimizes the advantages of debt while limiting the costs of debt that could put them in financial crisis. Despite extensive study, the expected impact of CEO domination on the relationship between creditor rights and capital structure has received little consideration. To solve this problem, the study sought to establish the effect of creditor rights on capital structure mediated by CEO power. The study aimed at determining the effect of creditor rights on capital structure, establish the effect of CEO power on capital structure and find out the mediating effect of CEO power on the relationship between creditor power and capital structure. A panel data and explanatory research design were used to conduct a survey of all the firms listed at Nairobi securities exchange. The total number of registered firms at NSE were 67 which made up the study population. The study focused on 40 firms that met the inclusion exclusion criterion over the period 2008-2020. This gave a total of 520 firm year observations. The study analyzed data obtained from secondary sources using a data analysis schedule. The study found that an increase in creditor rights, CEO power leads to firms borrowing more to finance their investments and assets. Also, there was partial mediation relationship between the creditor rights relationship and capital structure. The study concluded that creditor rights and CEO power had a positive and significant effect on capital structure and that, increase in these variables significantly increased debt ratio. The mediating effect showed a partial mediation and reduction in the relationship between creditor rights and capital structure.